Hypertension alters phosphorylation of VASP in brain endothelial cells. (1st June 2015) - Arlier, Zulfikar; Basar, Murat; Kocamaz, Erdogan; Kiraz, Kemal; Tanriover, Gamze; Kocer, Gunnur; Arlier, Sefa; Giray, Semih; Nasırcılar, Seher; Gunduz, Filiz; Senturk, Umit K.; Demir, Necdet
<x xml:space="preserve">Abstract</x> Hypertension impairs cerebral vascular function. Vasodilator-stimulated phosphoprotein (VASP) mediates active reorganization of the cytoskeleton via membrane ruffling, aggregation and tethering of actin filaments. VASP regulation of endothelial barrier function has been demonstrated by studies using VASP−/− animals under conditions associated with tissue hypoxia. We hypothesize that hypertension regulates VASP expression and/or phosphorylation in endothelial cells, thereby contributing to dysfunction in the cerebral vasculature. Because exercise has direct and indirect salutary effects on vascular systems that have been damaged by hypertension, we also investigated the effect of exercise on maintenance of VASP expression and/or phosphorylation. We used immunohistochemistry, Western blotting and immunocytochemistry to examine the effect of hypertension on VASP expression and phosphorylation in brain endothelial cells in normotensive [Wistar–Kyoto (WKY)] and spontaneously hypertensive (SH) rats under normal and exercise conditions. In addition, we analyzed VASP regulation in normoxia- and hypoxia-induced endothelial cells. Brain endothelial cells exhibited significantly lower VASP immunoreactivity and phosphorylation at the Ser157 residue in SHR versus WKY rats. Exercise reversed hypertension-induced alterations in VASP phosphorylation. Western blotting and immunocytochemistry indicated reduction in VASP phosphorylation in hypoxic versus normoxic endothelial cells. These results suggest that diminished VASP expression and/or Ser157 phosphorylation mediates endothelial changes associated with hypertension and exercise may normalize these changes, at least in part, by restoring VASP phosphorylation.